2009
DOI: 10.1016/j.biomaterials.2009.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric interpretation of protein adsorption: Kinetics of protein-adsorption competition from binary solution

Abstract: The standard solution-depletion method is implemented with SDS-gel electrophoresis as a multiplexing, separation-and-quantification tool to measure competition between two proteins (i and j) for adsorption to the same hydrophobic adsorbent particles (either octyl sepharose or silanized glass) immersed in binary-protein solutions. Adsorption kinetics reveal an unanticipated slow protein-size-dependent competition that controls steady-state adsorption selectivity. Two sequential pseudo-steady-state adsorption re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 73 publications
3
66
0
Order By: Relevance
“…Another interesting aspect of protein adsorption to bioceramics is competition adsorption between two or more proteins on the same adsorbent surface [223][224][225]. Leo Vroman firstly observed that fibrinogen preferentially adsorbed onto tantalum surfaces from blood plasma.…”
Section: Multi-protein Competition Adsorption and The Vroman Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting aspect of protein adsorption to bioceramics is competition adsorption between two or more proteins on the same adsorbent surface [223][224][225]. Leo Vroman firstly observed that fibrinogen preferentially adsorbed onto tantalum surfaces from blood plasma.…”
Section: Multi-protein Competition Adsorption and The Vroman Effectmentioning
confidence: 99%
“…However, certain proteins, such as human serum albumin, are observed to be relatively resistant to displacement at hydrophobic surfaces. The competitive adsorption of proteins is highly dependent on the concentrations and competing components [223,226]. Brash & Lyman [229] demonstrated that protein adsorption is in direct proportion to the protein concentration.…”
Section: Multi-protein Competition Adsorption and The Vroman Effectmentioning
confidence: 99%
“…Even though protein monolayer adsorption is a common hypothesis within the community of protein adsorption and biomaterials, there are also studies arguing for the possibility of proteins adsorbing in a multilayer fashion [9,15,[33][34][35]. Results from experiments with radioactive labelled proteins suggest that the hydrophobic PET surface can induce large conformational changes in adsorbed proteins and that those changes can induce enhanced adsorption of later arriving proteins onto the surface [24].…”
Section: Introductionmentioning
confidence: 95%
“…However, the mechanisms of the phenomenon are still debated and no existing model can fully explain it 17,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric effects, due to non-deformable proteins trying to fit on the available surface, can account for competitive adsorption of proteins 17 . However, they do not reproduce the maxima of absorption of the Vroman effect.…”
Section: Introductionmentioning
confidence: 99%